The Mental Status Exam: An Online Teaching Exercise Using Video-Based Depictions by Simulated Patients - Andrés Martin; Asaf Jacobs; Robert Krause; Doron Amsalem (Association of American Medical Colleges, 2020)
Introduction The mental status exam (MSE) is a structured approach to gathering a patient's behavioral and cognitive information. Analogous to the physical exam, it provides a template to collect clinical data in a systematic fashion. The MSE is a core competency of undergraduate medical education (UME) and an entrustable professional activity in clinical psychiatry. Methods We developed video clips of simulated patients depicting three adults respectively diagnosed with schizophrenia, obsessive-compulsive disorder, and bipolar disorder. We used three short video clips per condition to demonstrate an incremental number of psychiatric signs and symptoms. We used the nine video clips as calibrated stimuli for learners to identify components of the MSE using an online tool. Results We piloted this online exercise among 37 volunteer students. Experienced learners performed better than novice ones on overall identification of MSE components (p <.001). Specifically, they were able to identify elements of the MSE following an ABC-STAMPS (appearance, behavior, cooperation; and speech, thought process and content, affect, mood, perceptions, suicidality) rubric. Discussion This video-based scoring tool was easy to implement in a UME setting and well received by students as a formative didactic exercise and educational complement.